MICRO SIMULATION OF PELICAN CROSSING AT THE ROAD SECTION OF COLOMBO STREET, YOGYAKARTA - Anggraeni Hapsari; Siti Malkhamah (Journal of the Civil Engineering Forum, 2012)
Yogyakarta has a problem related to pedestrians. The inappropriate implementation of crossing facility and disobedience of pedestrians while crossing the street leads to conflicts between pedestrians and vehicular traffic. Taking the road section of Colombo Street as the case study, this research proposed pelican crossing with independent and coordination time signal operation. Using Aimsun software, the existing traffic signal, geometric design, traffic flow and turning proportion were taken into account to build the initial model. Afterwards, a calibration of queue length and a validation of vehicle speed were carried out to obtain a basic model which represents the existing condition of the system. Comparing the basic model and the alternatives in terms of performances of junctions, road section and pedestrians in the pelican, this research resulted in setting double cycling of pelican as 100 seconds for the independent operation and setting common cycle time 120 seconds for the coordination operation as the best alternatives. In addition, the implementation of pelican crossing brought about the reduction of vehicle speed in the road section so that the safety of pedestrian increased. Keywords: Pedestrian, pelican crossing, Aimsun, signal time, speed